Langobardia maior et minor: indagini sul legame tra la scultura altomedievale e i capitelli campani (Fenestella. Inside Medieval Art, 2021)
Langobardia maior et minor: indagini sul legame tra la scultura altomedievale e i capitelli campani.Within the southern Italian city of Capua – in the 10th and 11th century ruler's residence of the Lombard principality of Benevento and capital of Langobardia minor – a group of early medieval capitals has survived, which can be divided into three closely related types. On the basis of type I, which is bound to the corinthian capital, an examination will be made regarding to what extent relationships can be verified with the architectural sculpture of the older Lombard kingdom in northern Italy, which was incorporated into the Frankish Empire by Charlemagne as early as 774.For this purpose, certain technical and stylistic characteristics can be used, which concern in particular the overlapping tips of the acanthus leaves. The thesis is that in the very specific forms of Capuan capitals a line of tradition can be traced that is also found in other contexts of early medieval art in Campania, possibly with origins in the north.
Keywords: Capitals; Langobardia minor; Salerno; Arechis II; Early medieval sculpture